Genetic analysis of intestinal polyp development in Collaborative Cross mice carrying the ApcMin/+ mutation. Issue 1 (December 2016) - Dorman, Alexandra; Baer, Daria; Tomlinson, Ian; Mott, Richard; Iraqi, Fuad
Abstract Background Colorectal cancer is an abnormal tissue development in the colon or rectum. Most of CRCs develop due to somatic mutations, while only a small proportion is caused by inherited mutations. Familial adenomatous polyposis is an inherited genetic disease, which is characterized by colorectal polyps. It is caused by inactivating mutations in theAdenomatous polyposis coli gene. Mice carrying and non-sense mutation inAdenomatous polyposis coli gene at site R850, which designatedApc R850X/+ (Min ), develop intestinal adenomas, while the bulk of the disease is in the small intestine. A number of genetic modifier loci ofMin have been mapped, but so far most of the underlying genes have not been identified. In our previous studies, we have shown that Collaborative Cross mice are a powerful tool for mapping loci responsible for phenotypic variation. As a first step towards identification of novel modifiers ofMin, we assessed the phenotypic variation between 27 F1 crosses between different Collaborative cross mice and C57BL/6-Min lines. Results Here, C57BL/6-Min male mice were mated with females from 27 Collaborative cross lines. F1 offspring were terminated at 23 weeks old and multiple phenotypes were collected: polyp counts, intestine length, intestine weight, packed cell volume and spleen weight. Additionally, in eight selected F1 Collaborative cross-C57BL/6-Min lines, body weight was monitored and compared to control mice carry wildtypeAdenomatous polyposis coli gene. We found significant (p  < 0.05) phenotypic variation between the 27 F1 Collaborative cross-C57BL/6-Min lines for all the tested phenotypes, and sex differences with traits; Colon, body weight and intestine length phenotypes, only. Heritability calculation showed that these phenotypes are mainly controlled by genetic factors. Conclusions Variation in polyp development is controlled, an appreciable extent, by genetic factors segregating in the Collaborative cross population and suggests that it is suited for identifying modifier genes associated withApc Min/+ mutation, after assessing sufficient number of lines for quantitative trait loci analysis.